Pelatihan Produksi Sample Pakaian dengan Pola Digital di LPK Nadya Jaya Duri Kosambi - Susi Hartanto; Injo Erlyn Yulita (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2019)
With apparel import restriction, government has stated their supports for micro businesses to have a better growth. Supports need to be balanced by local competitiveness so that fashion business owners no longer feel the need to import from neighboring countries, such as Vietnam, China, or Thailand. Taking community service partner, LPK Nadya Jaya, UPH Product Design tries to provide trainings to increase level of competitiveness in these forms: (1) communication jargons and information updates in fashion industry, (2) fashion business workflows and marketing calendar for Indonesian e-commerce platform, (3) giving awareness that digital methods can be used to accelerate sample making process through case studies, (4) exposure on supplier performance from other countries. These trainings are compiled as a first step from a 3-year community service plan. The result on this first period are co-creation of 7 basic slopers and 9 ready-to-wear patterns, all in digital forms along with the samples.